2007
DOI: 10.1080/13880200601112885
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro. Investigation of the Protective Effects of Tannic Acid Against the Activities ofNaja kaouthia. Venom

Abstract: The in vitro venom neutralizing capacity of tannic acid against the activities of Naja kaouthia (Naja naja kaouthia Lesson [Elapidae]) venom was investigated. Tannic acid was found to be effective in neutralizing the activities of Naja kaouthia (NK) venom. The lethal effect of four-times the LD 50 in mice and the necrotizing effect of one minimum necrotizing dose (1 MND) in rats of NK venom were fully inhibited by tannic acid at !431 mg=mouse, with the median effective dose (ED 50) of 334 mg=mouse and !30 mg=r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…When tannins are present [HA(+)] the extract is able to neutralize the neuromuscular blockade promoted by Bjssu venom (n = 4). The protective effect of commercially available tannic acid was already demonstrated in vivo after subcutaneous injection in mice envenomed with Crotalus adamanteus venom (decreased hemorrhage, creatine kinase release and lethal activity) [ 27 ], or after its pre-incubation for 1 h at 37 ºC with Naja kaouthia Lesson (Elapidae) venom before intravenous injection in mice [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…When tannins are present [HA(+)] the extract is able to neutralize the neuromuscular blockade promoted by Bjssu venom (n = 4). The protective effect of commercially available tannic acid was already demonstrated in vivo after subcutaneous injection in mice envenomed with Crotalus adamanteus venom (decreased hemorrhage, creatine kinase release and lethal activity) [ 27 ], or after its pre-incubation for 1 h at 37 ºC with Naja kaouthia Lesson (Elapidae) venom before intravenous injection in mice [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…In regard to this issue, tannins and tannic acid share identical properties since both promote the precipitation of proteins [ 29 ]. Tannic acid has been already proved to precipitate proteins present in several snake venoms including venoms of the Elapidae family ( Naja kaouthia ) [ 28 ] and the Viperidae family ( C.d. terrrificus, Bothrops jararacussu ) [ 16 ] and Crotalus adamanteus [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro treatment showed that tannic acid caused dose-dependent AChE inhibition significantly, such that 0.04 mM of tannic acid reduced the AChE activity to 37% of the control in the nervous tissue of L. acuminata [ 92 ]. In addition, another in vivo research on AChE activity showed that tannic acid completely neutralized the AChE activity in Naja kaouthia venom [ 96 ].…”
Section: Terminalia Chebula Retziusmentioning
confidence: 99%
“…Pithayanukul et al [6], reported in vitro investigation of the protective effects of tannic acid against the action of Naja kaouthia venom. Melo et al [7] demonstrated the effectiveness of tannic acid in precipitating the constituent proteins of the complex mixture of snake venom (Bothrops jararacussu and Crotalus durissus terrificus).…”
Section: Introductionmentioning
confidence: 99%